Differences in the management and survival of metastatic colorectal cancer in Europe. A population-based study. Issue 5 (May 2021) - Bouvier, Anne-Marie; Jooste, Valérie; Sanchez-Perez, Maria José; Bento, Maria José; Rocha Rodrigues, Jessica; Marcos-Gragera, Rafael; Carmona-Garcia, Maria Carmen; Luque-Fernandez, Miguel Angel; Minicozzi, Pamela; Bouvier, Véronique; Innos, Kaire; Sant, Milena; et al.
Abstract: Background: The management regarding metastatic colorectal cancer throughout Europe is not well known. Aims: To draw a European comparison of the management and prognosis of metastatic colorectal cancers. Methods: Factors associated with chemotherapy administration were identified through logistic regressions. Net survival was estimated and crude probabilities of death related to cancer and other causes using a flexible cumulative hazard model. Results: Among the 13 227 patients with colorectal cancer diagnosed between 2010 and 2013 in cancer registries from 10 European countries, 3140 were metastatic. 62% of metastatic patients received chemotherapy. Compared to Spain, the related adjusted odds ratios ranged from 0.7 to 4.0 (P<0.001) according to country. The 3-year net survival by country ranged between 16% and 37%. The survival gap between countries diminished from 21% to 10% when adjusting for chemotherapy, age and sex. Geographical differences in the crude probability of death related to cancer were large for patients <70 or ≥80 years at diagnosis. Conclusion: Heterogeneity in the application of European guidelines partly explain these differences. General health between populations, accessibility to a reference centre, or provision of health care could also be involved. Further population-based studies are warranted to disentangle between these possible explanations.